1998
DOI: 10.1161/01.str.29.3.719
|View full text |Cite
|
Sign up to set email alerts
|

Brain Involvement in Scleroderma

Abstract: Background-Neuropathological data are very scarce in systemic sclerosis and fail to demonstrate primary changes in the brains of such patients. Case Descriptions-A 41-year-old woman with CREST syndrome developed signs of dementia after an episode of severe dehydration and died two months later of septic shock. A 63-year-old woman with CREST syndrome and a history of two unexplained transient ischemic attacks had had balance disorders since age 62. She died of severe pulmonary hypertension. In both cases, the a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
22
0
4

Year Published

1999
1999
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 50 publications
(27 citation statements)
references
References 13 publications
1
22
0
4
Order By: Relevance
“…Dermal sclerosis, as demonstrated on skin biopsy, has been associated with systemic sclerosis 11 ; however, neuropathological investigations in this condition have revealed calcification or necrosis rather than collagen deposition. 12,13 Our patient had none of the clinical features of focal dermal or systemic sclerosis, and biopsy revealed no evidence of calcification or necrosis, to suggest this as an underlying etiology. Periventricular venous collagenosis (PVC) has been described in elderly patients with leukoariosis but not stroke.…”
Section: Discussionmentioning
confidence: 73%
“…Dermal sclerosis, as demonstrated on skin biopsy, has been associated with systemic sclerosis 11 ; however, neuropathological investigations in this condition have revealed calcification or necrosis rather than collagen deposition. 12,13 Our patient had none of the clinical features of focal dermal or systemic sclerosis, and biopsy revealed no evidence of calcification or necrosis, to suggest this as an underlying etiology. Periventricular venous collagenosis (PVC) has been described in elderly patients with leukoariosis but not stroke.…”
Section: Discussionmentioning
confidence: 73%
“…13 Intracerebral calcification might result from necrosis of smooth muscle cells of the small cerebral arteries, which contain large amounts of calcium that could therefore be trapped and accumulate in the arterial wall. Cerebrovascular involvement often seems quiescent in scleroderma but might contribute to the onset of CNS disorders during low-flow states, as described in 1 patient, 3 or via vasospastic phenomena, revealed by serial angiography in a case report. 10 Increased vasospasm has been demonstrated in the main internal organs (heart, kidney, and lung) in scleroderma 11 and might explain why some middle-aged scleroderma patients have otherwise unexplained transient ischemic attacks with focal neurological defects 3,14,15 or transient global amnesia, 16 both of which were observed in our patients.…”
Section: Discussionmentioning
confidence: 89%
“…Cerebrovascular involvement often seems quiescent in scleroderma but might contribute to the onset of CNS disorders during low-flow states, as described in 1 patient, 3 or via vasospastic phenomena, revealed by serial angiography in a case report. 10 Increased vasospasm has been demonstrated in the main internal organs (heart, kidney, and lung) in scleroderma 11 and might explain why some middle-aged scleroderma patients have otherwise unexplained transient ischemic attacks with focal neurological defects 3,14,15 or transient global amnesia, 16 both of which were observed in our patients. In addition, various psychological disorders have been reported in scleroderma patients 15,[17][18][19] and may be partly due to organic brain involvement; indeed, it has recently been shown that patients with basal ganglia calcification frequently have neuropsychological alterations.…”
Section: Discussionmentioning
confidence: 89%
See 2 more Smart Citations